Distributed system for monitoring and forecasting of water bodies quality - Sanginova, Olga; Bondarenko, Sergii; Andriiuk, Valentyna; Kraieva, Kateryna (Lviv Politechnic Publishing House, 2017)
The structure and principles of constructing a distributed monitoring and forecasting system for water bodies quality designed to forecast the state of water supply sources in the remote mode are considered. The database of water bodies of Ukraine for storing the received data, including the data from the nongovernment and international organizations, is implemented. The interaction between the distributed subsystems is carried out via the client-server architecture.
Keywords: monitoring; distributed system; water body; water service